2018
DOI: 10.1002/pits.22179
|View full text |Cite
|
Sign up to set email alerts
|

A current landscape of specific learning disability identification: Training, practices, and implications

Abstract: Specific learning disability (SLD) identification procedures vary across states (Maki et al., 2015, School Psychol Quart, 30, 457–469); however, the extent to which SLD identification methods are implemented at the district level is not well understood. Moreover, the high‐stakes nature of SLD identification necessitates extensive training, but research regarding graduate and postgraduate training in SLD is limited. This study examined school psychologists’ SLD training and practices through survey methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 32 publications
3
33
1
1
Order By: Relevance
“…Many researchers proposed that the differences between males and females have to do with biological vulnerability; which means that males are more likely for being affected with LD than females (Moll et al, 2014;Pullen, 2016). Males tend to get more negative attention at school from educators because they externalize more symptoms related to LD as hyperactivity, impulsivity and physical aggression than females who often have different internalize symptoms such as anxiety, depression, daydreaming, and low self-esteem (Maki & Adams, 2018;Silver et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers proposed that the differences between males and females have to do with biological vulnerability; which means that males are more likely for being affected with LD than females (Moll et al, 2014;Pullen, 2016). Males tend to get more negative attention at school from educators because they externalize more symptoms related to LD as hyperactivity, impulsivity and physical aggression than females who often have different internalize symptoms such as anxiety, depression, daydreaming, and low self-esteem (Maki & Adams, 2018;Silver et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, psychologists and teachers were concerned about how to help those students to have better opportunities to use their potentials for better academic achievement (Aparna & Mahto, 2018). These efforts came as a response to an assumption that students with LD might be able to learn in different ways compared to their peers without LD, and as a result, a need emerged for modified teaching approaches and learning means that might be appropriate to the needs of those students (Maki & Adams, 2018). Many studies investigated learning as a human activity that takes place in different situations, in which individuals acquire and process information, and memorizes them to be later transformed into knowledge and skills that affect their behaviors (Moreau & Waldie, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These findings supported previous research which showed poor psychometric properties of PSW methods (McGill & Busse, 2017; Miciak et al, 2014; Stuebing et al, 2012), but contradicted the assertion that professional judgment results in improved SLD identification decisions using PSW (Flanagan & Schneider, 2016). Such findings are concerning given the increasing use of PSW in SLD identification (Maki & Adams, 2019). Thus, school psychologists should ensure that the SLD identification methods they use demonstrate empirical support.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although we provided participants with the DD/C framework from Flanagan et al (2018), we did not provide participants with access to computational software associated with the method (i.e., Cross-Battery Assessment System (X-BASS)). Although school psychologists have reported using DD/C without the X-BASS software in practice (Maki & Adams, 2019), and this is encouraged by proponents of this method (Flanagan et al, 2018), it is possible that using the X-BASS software could increase decision accuracy and confidence. Finally, whenever diagnostic efficiency statistics as per Kessel and Zimmerman (1993) are calculated within the context of SLD identification, it must be stipulated that no gold standard rule-in test has been developed; thus, these estimates should be regarded as our best estimate of how various identification methods likely operate in practice.…”
Section: Discussionmentioning
confidence: 99%